The Evaluation Exchange--Harvard Family Research Project - Brandon W. Youker (The Evaluation Center at Western Michigan University, 2005)
Harvard Family Research Project (HFRP) was founded by the Harvard Graduate School of Education in 1983. The HFRP aims to help strengthen family, school, and community partnerships of early childhood care and education; promote evaluation and accountability; and offer professional development to those who work with children and/or their families. The project has aided philanthropies, policymakers, and practitioners by collecting, analyzing, and synthesizing research and information.